The issues in academic library / Noor Farahain Abdul Razak and Nur Athirah Hanani Jailani - Abdul Razak, Noor Farahain; Jailani, Nur Athirah Hanani (Faculty of Information Management, 2015)
The academic libraries need to change the user perception about the libraries which is more to bad perception. Hence, to change that perception the academic libraries need to identify the issues that always occur in the libraries because it can easier the analysis process. Therefore, by doing the analysis, the libraries will know their problem such as lack in management and easier for them to overcome it. The first issue that always occurs in the academic library is about the collections. The other issue is the lack of the facilities. Besides that, the academic libraries do not develop the strategic planning. Furthermore, by developing the strategic planning, it can make the staff aware about their responsibilities, easy for the academic libraries to achieve their vision and mission and the management of the libraries will be more effective. In addition, the other issue is the relationship between the academic libraries and user is not strong enough. If the libraries want to gain a lot of benefits the director should play the important role. The customers and stakeholder also need to cooperate to ensure that all the efforts to change the library are successful.